2008
DOI: 10.1038/nprot.2008.75
|View full text |Cite
|
Sign up to set email alerts
|

Neutral red uptake assay for the estimation of cell viability/cytotoxicity

Abstract: The neutral red uptake assay provides a quantitative estimation of the number of viable cells in a culture. It is one of the most used cytotoxicity tests with many biomedical and environmental applications. It is based on the ability of viable cells to incorporate and bind the supravital dye neutral red in the lysosomes. Most primary cells and cell lines from diverse origin may be successfully used. Cells are seeded in 96-well tissue culture plates and are treated for the appropriate period. The plates are the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
1,239
0
22

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 1,815 publications
(1,270 citation statements)
references
References 14 publications
9
1,239
0
22
Order By: Relevance
“…This is supported by a previous study where Co not affected the viability of THP‐1 cells in concentrations up to 200 µM 31. As cytotoxicity test, NRU has previously been validated as a good technique for quantification of viable cells 44. Our results showed that IL‐1β released in the protein detection analysis was measured in noncytotoxic conditions.…”
Section: Discussionsupporting
confidence: 88%
“…This is supported by a previous study where Co not affected the viability of THP‐1 cells in concentrations up to 200 µM 31. As cytotoxicity test, NRU has previously been validated as a good technique for quantification of viable cells 44. Our results showed that IL‐1β released in the protein detection analysis was measured in noncytotoxic conditions.…”
Section: Discussionsupporting
confidence: 88%
“…This assay is based on the ability of viable cells to incorporate and bind the supravital dye neutral red in their lysosomes [29]. Differentiated LUHMES were seeded in 96 well culture plates and cultivated under differentiating conditions for 4 days as previously described.…”
Section: Lysosomal Integritymentioning
confidence: 99%
“…The cytotoxicity of rosuvastatine, doxazosin, repaglinide and oxcarbazepin was tested against MCF-7, HeLa and HepG2 cells by the neutral red assay as previously described (Repetto et al, 2008). Exponentially growing cells were collected using 0.25% Trypsin-EDTA and plated in 96-well plates at 1000-2000 cells/well.…”
Section: Cytotoxicity Assaysmentioning
confidence: 99%